Pengaruh Faktor-Faktor Psikososial dan Insomnia terhadap Depresi pada Lansia di Kota Yogyakarta - Carla R. Marchira, Ronny T. Wirasto, Sumarni DW (Berita Kedokteran Masyarakat (BKM), 2007)
Background: Even though depression among elderly is a common psychosociogeriatric problems, it needs to be taken seriously from the public health point of view. Many factors contributed to depression, among which are psychosocial factors (i.e. age, educational level, marital status, stressor, religious level, and social support) and physical and psychological problems.Objectives: The study was aimed to observe the influence of psychosocial factors (psychosocial stressor, social support, and religious level) and insomnia toward depression among elderly in Yogyakarta City.Material and Methods: The cross sectional study was conducted among elderly in Yogyakarta City. Instrument used in the study included: the Geriatric Depression Scale, the Psychosocial Stressor Study Instrument (IPSP), the Social Support questionnaire, the Mini Mental State Examination for cognitive screening; the KSPBJ InsomniaRating Scale; and praying instrument from KPDRY. Univariate analysis and multivariate stepwise logistic regression were used for this study.Results: A total of 128 elderly people were recruited into this study.  Mean age of respondent was 70.23 years (range: 60-88 years), with 32.8% respondents were male. Significant risk factors for depression included sex (p<0.05), age (p<0.05), education level (p=0.001), psychosocial stressor (p<0.001), religiousity level (p=0.001), insomnia (p<0.001), and social support (p<0.001). In the multivariate logistic regression, social support was identified as a significant factor with ap<0.001 and r2 of 61.9%.Conclusions: Social support is amongst the most important factors of depression among elderly in Yogyakarta CityKeywords: psychosocial factors, insomnia, depression, elderly people